2004
DOI: 10.1093/humrep/deh220
|View full text |Cite
|
Sign up to set email alerts
|

PCR-detected hepatitis C virus RNA associated with human zona-intact oocytes collected from infected women for ART

Abstract: HCV associated with unfertilized oocytes surrounded by their intact zona pellucida from anti-HCV antibody-positive and viraemic women undergoing ART raises questions concerning the safe management of medically assisted procreation for these women and good practice of oocyte/embryo cryopreservation and donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Hepatitis C virus (HCV) has been found in the FF of infected women (45) and was found to be associated with zona-intact oocytes from hepatitis C virus RNA-positive women undergoing IVF (including oocytes fertilized through ICSI) (46). But no cross-contamination of either of these viruses in embryo cryostorage has been reported.…”
Section: Evidence Of Risksmentioning
confidence: 99%
“…Hepatitis C virus (HCV) has been found in the FF of infected women (45) and was found to be associated with zona-intact oocytes from hepatitis C virus RNA-positive women undergoing IVF (including oocytes fertilized through ICSI) (46). But no cross-contamination of either of these viruses in embryo cryostorage has been reported.…”
Section: Evidence Of Risksmentioning
confidence: 99%
“…Therefore, the authors concluded that follicular fluid must be considered as potentially infected, but all oocytes can be inseminated by ICSI resulting in virus-free embryos in culture. In a smaller study, Papaxanthos-Roche et al (2004) found HCV associated with unfertilized oocytes denuded of follicular cells.…”
Section: Virus-positive Femalementioning
confidence: 90%
“…The aim of Papaxanthos-Roche's study [14] was to investigate the susceptibility of human oocytes from hepatitis C virus (HCV) RNA-positive women to HCV contamination during assisted reproductive technology (ART). A reverse transcriptase PCR assay was used to test for the presence of HCV RNA associated with 24 unfertilized oocytes 48 h after follicular fluid aspiration in 10 IVF attempts (seven conventional IVF and three ICSI).…”
Section: Discussionmentioning
confidence: 99%
“…A weak correlation was found between plasma and follicular fluid HCV RNA loads (r = 0.73, P \ 0.001). HCV associated with unfertilized oocytes surrounded by their intact zona pellucida from anti-HCV antibody-positive and viraemic women undergoing ART raises questions concerning the safe management of medically assisted procreation for these women and good practice of oocyte/ embryo cryopreservation and donation [14].…”
Section: Discussionmentioning
confidence: 99%